Risk Factors for Urinary Frequency in Taiwanese Women Aged 20-59 Years - Ching-Hung Hsieh; Hsing-Yu Chen; Chun-Sen Hsu; Shao-Tung Chang; Tsung-Cheng Kuo; Chien-Dai Chiang (Elsevier, 2006)
Objective: To evaluate the risk factors for daytime urinary frequency in Taiwanese women aged 20-59 years. Materials and Methods: In 1998, there were about 5.9 million female residents aged 29-59 years in Taiwan. A random sample of 4,549 women within this age group was chosen by multistage sampling. Face-to-face interviews with 3,537 women were completed by well-trained professional interviewers within 3 months of the subjects being selected. Answers to questions about lower urinary tract symptoms, sociodemography and past histories were recorded. The factors were assessed by frequency analysis and logistic regression analysis using a significance level of less than 0.05. Results: The prevalence of daytime urinary frequency was significantly related to diabetes mellitus (p = 0.038), hypertension (p = 0.016) and previous gynecologic surgery (p = 0.005). However, there was no relationship between urinary frequency and body mass index, drug allergy, smoking, alcohol consumption, marital status, childbirth, parity, hysterectomy, menopause, hormone replacement therapy or age. Conclusion: The results of this study show relatively high risk of urinary frequency development in patients with diabetes mellitus or hypertension. Better quality health education of these women, drawing their attention to the possibility of gynecologic surgery, is the most important factor in making current gynecologic surgery more effective. In addition, more attention given to associated factors that are preventable, modifiable or controllable, for example diabetes or hypertension, may have an impact on the prevalence of urinary frequency.